Anticipating a disrupted world: leavers for sustainable economic development - Gunathilaka, L.F.D.Z.; Gunawardana, K.D. (Faculty of Management Sciences, University of Sri Jayewardenepura, 2020)
This paper focuses on the inclusion of disruptive change risks in financial, social and environmental viability in the Rubber manufacturing process in Sri Lanka. The aim of this discussion is two-fold: firstly, examines the questions of long term financial feasibility risk in disruptive transition to a sustainable future. It discusses different anticipatory options that interface with resolving and/or managing this risk, as well as the implication for stakeholders. Secondly, this review is on the risk associated with mitigation, labelled as challenges of disruptive change and the associate long-term impact on the performance of assets and business portfolios. The hypothesized relationships of this model are tested with data collected from 30 rubber manufacturing firms in Sri Lanka by building panel models for the sample during the period of 2013-2017. This study found that in general, risk associate with mitigation does have a significant impact on firm performance and it also found that the risk associate with adaptation weakened the relationship between mitigation and firm performance.
Keywords: Disruptive change risk, Mitigation risk, Adaptation risk, Firm performance, Panel data, Rubber industry